Cancellable elements of the lattice of semigroup varieties - Gusev, S.V.; Skokov, D.V.; Vernikov, B.M. (Algebra and Discrete Mathematics, 2018)
We completely determine all commutative semigroup varieties that are cancellable elements of the lattice SEM of all semigroup varieties. In particular, we verify that a commutative semigroup variety is a cancellable element of the lattice SEM if and only if it is a modular element of this lattice.